The Effect of Lemon Aromatherapy, Nausea and Vomiting on Trimester I Pregnant Women in Paramitra Clinic - Puri Kresna Wati (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2021)
Background: Nausea and vomiting occur in 60-80% of primigravidas and 40-60% in multigravidas. The survey results obtained from 36 pregnant women 21 pregnant women experiencing nausea and vomiting. The research objective was to determine the effect of lemon aromatherapy on the intensity of nausea and vomiting in pregnant women in the first trimester of the Clinic and RB Paramitra Medika 1 in 2020.Sample and method: The study design was pre-experimental research design (one group pre-test and post-test design). The sample of pregnant women who experience nausea and vomiting is 30 pregnant women by quota sampling. The instrument used was the Standard Operating Procedure (SOP) and the PUQE SCORE questionnaire using the Paired Samples T-test with a significant level of 0.05.Result: The results showed that the pre-test mean value was 7.97 and posttest was 5.7 with an average decrease in the nausea and vomiting scale of 2.3, the statistical test obtained the t value for nausea and vomiting= 6.643 and p=0.000, where p<0.05, then H1 is accepted.Conclusion: There is an effect of lemon aromatherapy on the intensity of nausea and vomiting in pregnant women in the first trimester at the Paramitra Clinic.